2023
DOI: 10.46542/pe.2023.231.269282
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy students' perceptions and satisfaction with blended instruction in quantitative chemical analysis course

Abstract: Background: Course satisfaction in blended learning has become a priority among educators to keep students on track during their studies. This study investigated the Community of Inquiry (CoI) three key components, i.e. teaching, social, and cognitive presences and other factors that affect student satisfaction at Lebanese International University (LIU).     Objective: The study aimed to examine pharmacy undergraduate students who enrolled in, and the effect of blended learning courses on learning environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Fifth, blended learning environments must also focus on the proper distribution of online and offline activities. Sonji et al (2023) found that the majority of students appreciated clear course content, organization, instructional resources, course design, and orientation. The design approach as well as the division between online and classroom courses were the key factors influencing the satisfaction of university students with their learning experience.…”
Section: Blended Instructional Guidelines Based On Coi Frameworkmentioning
confidence: 98%
See 2 more Smart Citations
“…Fifth, blended learning environments must also focus on the proper distribution of online and offline activities. Sonji et al (2023) found that the majority of students appreciated clear course content, organization, instructional resources, course design, and orientation. The design approach as well as the division between online and classroom courses were the key factors influencing the satisfaction of university students with their learning experience.…”
Section: Blended Instructional Guidelines Based On Coi Frameworkmentioning
confidence: 98%
“…Teachers who struggle with blended courses can receive advice and encouragement from their peers about promising practices. Sonji et al (2023) also stated that a safe classroom learning climate contributes to student engagement and cognitive development. ElSayad (2023) suggested the importance of establishing a CoI framework in a blended learning environment by investigating the potential impact of the components of a community framework of inquiry on students' perceptions of learning.…”
Section: Features Of Teacher Instructional Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Online chemistry learning has been reported [8], but the use of CoI in chemistry education has not been extensively reported [7,[30][31][32]. There are even fewer studies on the use of CoI in pharmacy education [33,34]. Previously, we reported students' collective perception of asynchronous lectures via the CoI framework, and the relationship with the students' learning performance [35].…”
Section: Research Purpose and Questionsmentioning
confidence: 98%
“…With these research gaps, this study aims to extend previous studies involving Chemistry and Pharmacy courses [7,8,[30][31][32][33][34]. Additionally, the study also aims to determine whether the design features for designing asynchronous lectures can enhance students' engagement by minimizing transactional distance [28] in an asynchronous learning environment.…”
Section: Research Purpose and Questionsmentioning
confidence: 99%